In Vitro Effect of Low-level Laser Therapy on Candida albicans Colonies Isolated From Patients Undergoing Radiotherapy for Head and Neck Cancer: Low-level laser therapy for Candida albicans - Hasanah, Novia Tri; Sufiawati, Irna; Kusumadjati, Adji; Sunardi, Mas Adi (Journal of Lasers in Medical Sciences, 2024)
Introduction: Studies on head and neck cancer (HNC) patients undergoing radiotherapy have revealed increased numbers of Candida spp., leading to oral candidiasis and oral mucositis. The effects of laser therapy on Candida spp. have been studied with varied results. This study aimed to investigate the effect of low-level laser therapy (LLLT) on C. albicans colonies isolated from HNC patients undergoing radiotherapy. Methods: This study included a treated group, wherein 11 C. albicans isolates were obtained from the saliva of HNC patients undergoing radiotherapy at a dose exceeding 30 Gy. The control groups consisted of an untreated negative control and a positive control treated with nystatin. The treatment groups were subjected to LLLT in continuous mode for 50 seconds at a wavelength of 976 nm, 0.1 W at a dose of 5 J/cm2 for Laser 1 (L1) group and 0.2 W at a dose of 10 J/cm2 for Laser 2 (L2) group. The tests were conducted using C. albicans inoculum equivalent to a 0.5-McFarland suspension on 96-well plates. All test group inoculums were then cultured on Sabouraud dextrose agar (SDA), and the colony count was assessed at 104 CFU/mL. Results: LLLT at 5 and 10 J/ cm2 reduced C. albicans colonies by 7.01% and 10.94%, respectively, but the reductions were not statistically significant (P>0.05). Nystatin eliminated all the colonies. Conclusion: LLLT shows potential for reducing C. albicans colonies in HNC patients undergoing radiotherapy. However, further studies with varied parameters and methods are necessary.